Additive manufacturing and testing of a soft magnetic rotor for a switched reluctance motor - Gargalis, Leonidas; Madonna, Vincenzo; Giangrande, Paolo; Rocca, Roberto; Hardy, Mark; Ashcroft, Ian; Galea, Michael; Hague, Richard (Institute of Electrical and Electronics Engineers Inc., 2020)
Additive manufacturing is acknowledged as a key enabling technology, although its adoption is still constrained to niche applications. A promising area for this technology is the production of electrical machines (EMs) and/or their main components (e.g. magnetic cores, windings, heat exchangers, etc.) due to the potential of creating lightweight, highly efficient rotating motors, suitable for applications requiring a low moment of inertia. This work investigates the readiness of metal additive manufacturing, specifically Laser Powder Bed Fusion (LPBF), applied to the field of EMs to bridge the gaps of how to use this technological approach in this field. A soft magnetic material featuring high silicon content (Fe-5.0%w.t.Si) has been developed for LPBF and a rotor has been 3D-printed for a switched reluctance machine. The printed rotor was assembled into a conventionally laminated stator and the performance of the whole machine was evaluated. Its performance was compared against an identical machine equipped with a laminated rotor of the same dimensions made of conventional non-oriented silicon steel. A comparative study was carried out through both finite element simulations and experimental tests. The efficiency of the two machines was assessed together with the principal electrical and mechanical quantities under several operating conditions.